Gambaran Perilaku Hidup Bersih dan Sehat (PHBS) Ibu dengan Kejadian Penyakit Diare pada Balita di Wilayah Kerja Puskesmas Umanen Kabupaten Belu - Mariana P. Bria; Ribka Limbu; Tanti Rahayu; Petrus Romeo (Yayasan Literasi Sains Indonesia, 2025)
Diarrhea is a disease in which a person experiences consistent changes in feces to be more liquid than usual but not bloody with a frequency of more than three times within 24 hours. This study aims to determine the description of Clean and Healthy Living Behavior (PHBS) of Mothers with the Incidence of Diarrhea in Toddlers in the Umanen Health Center Working Area, Belu Regency. This type of research is descriptive research that is studied quantitatively. The sample in this research was 60 mothers. Sampling in this study using total sampling technique. The results showed that the use of clean water was categorized as good with a percentage of 56.7%, hand washing behavior was categorized as poor with a percentage of 55.0%, the behavior of throwing garbage in place was categorized as poor with a percentage of 53.3% and the behavior of using healthy latrines was categorized as poor with a percentage of 63.3%. For mothers of toddlers, it is hoped that they will always apply PHBS (Clean and Healthy Living Behavior) by applying the 7 steps of Hand Washing with Soap (CTPS) which is good and correct and further apply the behavior of disposing of garbage in its place and applying the use of healthy latrines in everyday life.